Contributions to the knowledge of the myrmecophilous pselaphines (Coleoptera, Staphylinidae, Pselaphinae) from China. I. Tangius glabellus gen. et sp. nov. from Tibet - Yin, Zi-Wei; Li, Li-Zhen; Zhao, Mei-Jun (Zootaxa, 2012)
Tangius glabellus Yin & Li, a new myrmecophilous genus and species of the subtribe Batrisina, is described and illustratedfrom Tibet, Southwest China, and its taxonomic placement is discussed. Brief biological information on the new species is provided.